Length-dependent stability and strand length limits in antiparallel β-sheet secondary structure - Stanger, Heather E. (The National Academy of Sciences, 2001)
Designed peptides that fold autonomously to specific conformations in aqueous solution are useful for elucidating protein secondary structural preferences. For example, autonomously folding model systems have been essential for establishing the relationship between α-helix length and α-helix stability, which would be impossible to probe with α-helices embedded in folded proteins. Here, we use designed peptides to examine the effect of strand length on antiparallel β-sheet stability. α-Helices become more stable as they grow longer. Our data show that a two-stranded β-sheet (“β-hairpin”) becomes more stable when the strands are lengthened from five to seven residues, but that further strand lengthening to nine residues does not lead to further β-hairpin stabilization for several extension sequences examined. (In one case, all-threonine extension, there may be an additional stabilization on strand lengthening from seven to nine residues.) These results suggest that there may be an intrinsic limit to strand length for most sequences in antiparallel β-sheet secondary structure.